Comparison of NGS and MFC methods: key metrics in multiple myeloma MRD assessment - Kriegsmann, Katharina; Hundemer, Michael; Hofmeister-Mielke, Nicole; Reichert, Philipp; Manta, Calin-Petru; Awwad, Mohamed; Sauer, Sandra; Bertsch, Uta; Besemer, Britta; Fenk, Roland; Hänel, Mathias; Munder, Markus; et al. (Cancers, 2020)
In order to meet the challenges in data evaluation and comparability between studies in multiple myeloma (MM) minimal residual disease (MRD) assessment, the goal of the current study was to provide a step-by-step evaluation of next-generation sequencing (NGS) and multicolor flow cytometry (MFC) data. Bone marrow (BM) sample pairs from 125 MM patients were analyzed by NGS and MFC MM MRD methods. Tumor load (TL) and limit of detection (LOD) and quantification (LOQ) were calculated. The best-fit MRD cut-off was chosen as 1 × 10−5, resulting in an overall 9.6% (n overall = 12 (NGS n = 2, MFC n = 10)) nonassessable cases. The overall concordance rate between NGS and MFC was 68.0% (n = 85); discordant results were found in 22.4% (11.2% (n = 14) of cases in each direction. Overall, 55.1% (n = 60/109) and 49.5% (n = 54/109) of patients with a serological response ≥ very good partial response (VGPR) showed BM MRD negativity by NGS and MFC, respectively. A good correlation in the TL assessed by both techniques was found (correlation coefficient = 0.8, n = 40, p < 0.001). Overall, our study shows good concordance between MM BM MRD status and TL when comparing NGS and MFC at a threshold of 10–5. However, a sufficient number of analyzed events and calculation of MRD key metrics are essential for the comparison of methods and evaluability of data at a specific MRD cut-off.